Cloud-assisted rendering support for mobile online gaming - Quek, Tommy Teck Soon (2015)
Computer games have been rather popular for the past decades ever since personal computers came about. The increasing interactivity and graphics of the game often requires an upgrade on the current computer. However, this issue can be resolved by allowing computer games to be streamed online, otherwise known as online mobile games. Cloud technology allows the use of computers with much larger computation capacity. By shifting the heavy computation process to the cloud server, the current “fat” client would become much thinner. Basically what the client need would be an internet service provider providing internet connection with a computer that is enough to support the video stream. This project will be focusing on the supporting features for the current implemented cloud assisted gaming platform which handles the recording of the user gameplay experience. This recording application would be dynamic and user-friendly which works modularly with the games application. The application allows game developers to develop games separately as the recording needs only the current video stream of the gameplay. This would be very crucial to the platform as reusability would be needed in this application. As such, this project focuses considerably on the application architecture.